Inducing lattice defects in calcium ferrite anode materials for improved electrochemical performance in lithium-ion batteries. Issue 9 (1st May 2022) - Sanad, Moustafa M.S.; Azab, A.A.; Taha, T.A.
Abstract: Enhancing the electrical conductivity of electrode materials via a cationic substitution strategy was recognized as an effective way of improving the electrochemical performance of Li-ion batteries. Thus, Lix Ca1-x Fe2 O4 nanoparticles were synthesized via a facile inexpensive process at low temperature. XRD peaks refer to the formation of an orthorhombic structure with the Pnma space group. HR-TEM investigations reveal orthorhombic-like shape for pure CaFe2 O4, nanoplatelet-like morphology for Li0.05 Ca0.95 Fe2 O4 and irregular distorted crystals for Li0.1 Ca0.9 Fe2 O4 . Voids and pores in Li-doped CaFe2 O4 were confirmed by FESEM and BET measurements. XPS spectra of O1s prove that Li-doped CaFe2 O4 have higher conductivity due to the created lattice defects and oxygen species. Li-doped CaFe2 O4 anodes exhibit great improvement in their initial discharge capacities ∼1219 and 1606 mAhg −1 upon substitution of Ca with 5% and 10% Li, respectively. Furthermore, 10% Li-doped CaFe2 O4 anode displays the highest Li-ions diffusion coefficient and exchange current density due to the enhanced Li + ions mobility. Moreover, the DC activation energies for the Lix Ca1-x Fe2 O4 nanoparticles decreased with increasing Li content.